The volume and timing of upper limb movement in acute stroke rehabilitation: still room for improvement. Issue 22 (22nd October 2020) - McLaren, Ruth; Signal, Nada; Lord, Sue; Taylor, Steve; Henderson, Jeanette; Taylor, Denise
Abstract: Objective: To observe upper limb activity patterns of people with stroke during sub-acute rehabilitation to inform the development of treatment strategies for upper limb rehabilitation. Design: Observational study of upper limb activity. Methods: Twenty participants admitted for sub-acute rehabilitation following stroke were observed during a week day for 1 minute every 10 min between 7 am and 7 pm. Upper limb activity was recorded and categorized into five types of movement. Results: Participants used either one or both upper limbs for 45.8% of the observation time. The affected arm moved 26.4% of the time, with most movement occurring in conjunction with the unaffected arm (18.9% of the time) and only 7.5% of the time being movement of the affected arm by itself. The largest proportion of upper limb activity was observed during mealtimes. Conclusions: Recognition of the need to improve upper limb outcomes after stroke has not yet translated into changes in the amount of upper limb activity undertaken during sub-acute rehabilitation. Opportunities to rehabilitate the hemiplegic upper limb are not fully realized. The dominance of bilateral movement in the early stages after stroke may provide scope for interventions that maximize this aspect of motor control. IMPLICATIONS FOR REHABILITATION: Despite advances in rehabilitation, time spent in upper limb activity following stroke is very low, particularly in the affected arm. Most movement of the affected arm occurs in conjunction with the unaffected arm. There is an urgent need to redress this low level of movement, given the importance of upper limb recovery to quality of life for people following stroke.